The study of acute toxicity of burdock root tincture - T. V. Оproshanska (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. Burdock root is used in scientific medicine as diuretic, choleretic, antipyretic, anti-inflammatory, antibacterial, antifungal, desensitizing, immunostimulatory, antioxidant and metabolism improving remedy. To study acute toxicity of the Burdock root tincture (extractant is a 40% ethanol) at the terms of single internally gastric injection at 5 ml/kg, 15 ml/кg and 20 ml/kg dose, 84 white rats and 84 mice of both sexes (14 groups which consist of 6 animals) have been used.